DESIGN AND IN VITRO EVALUATION OF ORALLY DISINTEGRATINGTABLETS OF SELEGILINE - Yellanki, Shiva Kumar (International Journal of Current Pharmaceutical Research, 2015)
Objective: The purpose of presenting research work to formulate oral disintegrating tablets of Selegiline to enhance therapeutic efficacy. Methods: An attempt has been made to develop and evaluate Orally Disintegrating or Mouth Dissolving tablets of Selegiline for quick effect, better patient compliance and effective therapy. Fast dissolving tablets of Selegiline were prepared by direct compression technique using selected super disintegrants. Results: The FTIR spectra revealed that, there was no interaction of drug with formulation ingredients. The prepared tablets were evaluated for drug content, friability, hardness, In vitro disintegration and In vitro release studies. All the tablets with different super disintegrants showed better results. However, required disintegration and dissolution behavior of Selegiline was achieved for tablets with Crospovidone (20%) as super disintegrant. Conclusion: From experimental studies it is concluded that fast dissolving drug delivery systems can be a suitable approach to improve onset of action for getting instantaneous therapeutic response.